Visions, ideals and elections: The struggle for political apartheid within the Nationalist alliance, 1948-1959 - McIntosh, Robert (My University, 1996)
This paper accepts the major conclusions of Posel, Lazar and others that there did not exist prior to the Nationalists assuming power a plan sufficiently coherent to facilitate its execution by legislators and administrators in the sense of following a "blueprint", and that the Nationalists in government faced numerous political and practical difficulties in their endeavours to translate their aspirations for apartheid into a practical programme. For Lazar, the Nationalist alliance was comprised of factions and classes, "all of whom saw their interests in different ways". The new government sought to develop its policy of apartheid, against a background of the need to keep the alliance together, and to counter escalating African resistance. Lazar describes an ideological struggle between the "visionaries" in the South African Bureau of Racial Affairs (SABRA) and the government, especially in the person of Verwoerd. The struggle lasted throughout the 1950s, until Verwoerd, with the backing of the Broederbond, succeeded in purging SABRA, and capturing it for the, then, Verwoerd-led government. SABRA had endeavoured to invent an ideology for its grand plan, and one which represented a search for a consistent moral position for complete separation. The SABRA vision was dependent upon total separation, which could not be applied to an economic system which used cheap African labour to perpetuate white domination. Posel has argued that the class divisions within the Nationalist alliance generated different "blueprints" for apartheid. Total segregation was espoused by powerful factions comprising Afrikaner intellectuals, particularly among the membership of SABRA. Posel defined the SABRA intellectuals as "purists", as opposed to the members of the government who were pragmatic, and more conciliatory to the needs of industrial and commercial capital for a stable, urbanised labour force. The new government also had to contend with other problems; policy-making and implementation were shaped and constrained by the relations between the government and the largely UP-controlled municipal authorities, and the dominating ideological factions within the Native Affairs Department (NAD). Despite these largely class divisions, the Nationalist Alliance could unite behind a programme of the political disenfranchisement of Africans which was seen as essential to the maintenance of white supremacy.
African Studies Seminar series. Paper presented 20 May 1996
Keywords: Apartheid. South Africa; South Africa. Politics and government. 1948-1961